Effects of liming on soil properties, leaf tissue cation composition and grape yield in a moderately acid vineyard soil. Influence on must and wine quality - Quiroga, Miguel J.; Olego, Miguel A.; Sanchez-Garcia, Mario; Esteban Medina, Jesus; Visconti, Fernando; Rubio Coque, Juan J.; Garzón-Gimeno, Enrique (2018)
Aims: Soil acidity decreases soil fertility and grapevine growth. Aluminum toxicity has been recognized as one of the most common causes of reduced grape yields in acid vineyard soils. The main aim of this study was to evaluate the effect of two liming materials, i.e. dolomitic lime and sugar foam, on a vineyard cultivated in an acid soil. Methods and results: The effects were studied in two soil layers (0-30 and 30-60 cm), as well as on leaf nutrient contents, grape yield, and must and wine quality properties, in a vineyard dedicated to Vitis vinifera L. cv. Mencia cultivation. The data management and analysis were carried out using ANOVA. Conclusion: Sugar foam was more efficient than dolomitic limestone as liming material since it induced the highest decrease in soil acidity properties at the same calcium carbonate equivalent dose. Effects of liming on leaf nutrient contents, grape yield, and must and wine quality properties were barely observed. Significance and impact of the study: Until recently, little was known about the effects of liming on both vine nutritional status and must/wine quality properties. Thus, this research fills an important knowledge gap.